Prophetic parenting training for mothers as an effort to overcome the problem of online game addiction - Fitria Istikhomah; Cherilla Kapindanu; Hersi Agustin; Yanu Ainur Fitri; Zilla Fazzira; Mariyati Mariyati (Universitas Muhammadiyah Magelang, 2022)
In the modern era, science and technology are developing very quickly. One example is the internet. Online game addiction is one of the harmful effects of internet development. To stop this horrible thing, parents play a critical role. Peers and other external factors can also be destructive. The purpose of this community service project is to improve parents' awareness of prophetic parenting. It is believed that parents will be able to use this knowledge in their daily lives to reduce the number of children who become addicted to online games. This community service is carried out through health education about the dangers of online game addiction and the practice of prophetic parenting through 6 stages. As many as 20 SDN Krapyak Semarang City guardians participated in this exercise. The service's outcomes revealed an improvement in parenting abilities using the prophetic parenting approach as well as increased understanding about the negative effects of online game addiction on students' mental health.